DEVELOPMENT OF TEACHING MATERIALS FOR BANK AND NON-BANK FINANCIAL INSTITUTIONS COURSES - Indah Permatasari; Astuti, Ratna Fitri (Faculty of Teacher Training and Education, Mulawarman University, 2023)
The learning facilities and resources used in the learning process for Banking and Non-Bank Financial Institutions courses are very limited in terms of the quantity available. and has not represented PIP Unmul, namely Humid Tropical Forests and Their Environment. so the impact on interaction between students and learning resources is still not optimal. The development model used in this research is the research and development model. ADDIE development model (analysis, design, development and implementation, and evaluation). The types of data used in this research are qualitative data and quantitative data. Qualitative data was obtained from interview data from lecturers and students. The results of product feasibility validation tests obtained a score of 95.15% and practitioners obtained a score of 93.47%. The results of the small group trial obtained a score of 77.25%, which means the media was very interesting, while the effectiveness of the media showed that 87.88% of students obtained a score ≥ 70. The subjects in this field test were 62 students, which were measured using 10 indicators with average results. falls into the good category. The effectiveness of books can be measured from student learning activities in achieving learning goals through learning outcomes. In conclusion, the teaching materials developed are able to have a positive impact on the implementation of the learning process.